2012
DOI: 10.1364/ol.37.003231
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh laser pulse energy and power generation at 10 kHz

Abstract: This Letter presents results from a new master-oscillator, power-amplifier pulse-burst laser system demonstrating ultrahigh pulse energies greater than 2.0 J/pulse at 1064 nm with interpulse separations of 100 μs (10 kHz) for burst durations of 100 pulses. Each pulse generates peak powers exceeding 130 MW and an average power of approximately 20 kW is generated over a 100-pulse-burst. Pulse energies decrease by less than 10% over a 100 sequential pulses, demonstrating negligible "droop" over long-duration puls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…It appears from the formaldehyde layer thicknesses, both normal to and in the direction of flame propagation, that these effects are negligible for the current conditions. As shown in Table 1, the image series reported in this work represents a fivefold improvement in TDR over prior burst-mode PLIF measurements, which have been limited either in burst duration or repetition rate [4][5][6][7][8][9][10][11][12][13][14][15][16]. The measured SNR of 30 without pixel binning is comparable to those previously reported pulse-burst formaldehyde PLIF sequences [4,12] as well as to those in which pixel binning was employed [8].…”
supporting
confidence: 74%
See 2 more Smart Citations
“…It appears from the formaldehyde layer thicknesses, both normal to and in the direction of flame propagation, that these effects are negligible for the current conditions. As shown in Table 1, the image series reported in this work represents a fivefold improvement in TDR over prior burst-mode PLIF measurements, which have been limited either in burst duration or repetition rate [4][5][6][7][8][9][10][11][12][13][14][15][16]. The measured SNR of 30 without pixel binning is comparable to those previously reported pulse-burst formaldehyde PLIF sequences [4,12] as well as to those in which pixel binning was employed [8].…”
supporting
confidence: 74%
“…The TDR reported in the current work and that of previous burst-mode measurements is summarized in Table 1 for comparison [4][5][6][7][10][11][12][13][14][15][16]. For many turbulent reacting flows of practical interest, a 10 ms time duration represents multiple cycles of fluctuations in the vector and scalar fields under investigation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5(b) and 5(d). These parameters were used to generate up to 30 mJ pulse energy at 354.8 nm over a 30-ms burst duration, which captures transients that evolve over a longer time period than those observable with the 10-ms bursts achieved in previous work [22,24]. In this case the repetition rate was reduced to 5 kHz in order to maintain sufficient pulse energy near the end of the burst, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This system increased the duration of previously published burst-mode laser sequences by nearly tenfold with sufficient energy in a burst of 200 pulses to perform 20-kHz formaldehyde PLIF for the first time in a lifted methane-air diffusion flame. Subsequently, Fuest et al demonstrated a 10-kHz, 10-ms burst duration PBL system with up to 200 J per burst based on a solid-state pulsed master oscillator amplified through a chain of eight flashlamp amplifiers [24], although its utility for planar measurements was not evaluated.…”
Section: Introductionmentioning
confidence: 99%